PERAN MODERASI SELF-COMPASSION TERHADAP HUBUNGAN ANTARA SOCIAL ANXIETY DAN SOCIAL MEDIA ADDICTION PADA DEWASA AWAL PENGGUNA MEDIA SOSIAL - Jason Dionnicius Young; Sandi Kartasasmita (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Social media has become an integral part of life in the digital era, but its use may also lead to negative consequences, one of which is social media addiction. Social anxiety is one of the factors contributing to social media addiction, as individuals with social anxiety tend to use social media as an escape from negative experiences and social situations that create psychological distress. Self-compassion is assumed to play a role in this relationship because it is associated with an individual’s ability to accept personal shortcomings and respond to difficult experiences more adaptively. This study aimed to examine the moderating role of self-compassion in the relationship between social anxiety and social media addiction among young adult social media users. This study employed a quantitative approach using purposive sampling involving 419 young adult participants. Data were collected using the Indonesian Bergen Social Media Addiction Scale (α = .762), the Indonesian version of the Liebowitz Social Anxiety Scale–Self Report (α = .955), and the Self-Compassion Scale (α = .828), and were analyzed using moderated regression analysis. The results showed that self-compassion moderated the relationship between social anxiety and social media addiction. This finding may be explained by the presence of the negative dimensions of self-compassion, such as self-judgment, isolation, and overidentification, which may actually exacerbate social anxiety and increase the tendency toward social media addiction. ABSTRAK Media sosial telah menjadi bagian integral dalam kehidupan di era digital, tetapi penggunaannya juga dapat menimbulkan dampak negatif, salah satunya social media addiction. social anxiety merupakan salah satu faktor yang berkontribusi terhadap social media addiction, karena individu dengan kecemasan sosial cenderung menggunakan media sosial sebagai sarana pelarian dari pengalaman negatif dan situasi sosial yang menimbulkan tekanan psikologis. self-compassion diduga berperan dalam hubungan tersebut karena berkaitan dengan kemampuan individu untuk menerima kekurangan diri dan merespons pengalaman sulit secara lebih adaptif. Penelitian ini bertujuan untuk menguji peran moderasi self-compassion dalam hubungan antara social anxiety dan social media addiction pada dewasa awal pengguna media sosial. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik purposive sampling pada 419 partisipan dewasa awal. Data dikumpulkan menggunakan Indonesian Bergen Social Media Addiction Scale (α = .762), Liebowitz social anxiety scale–self report versi Bahasa Indonesia (α = .955), dan Skala Welas Diri (α = .828), kemudian dianalisis menggunakan moderated regression analysis. Hasil penelitian menunjukkan bahwa self-compassion memoderasi hubungan antara social anxiety dan social media addiction. Penemuan ini dapat dijelaskan melalui adanya dimensi negatif self-compassion, seperti self-judgment, isolation, dan overidentification, yang justru dapat memperburuk kecemasan sosial dan meningkatkan kecenderungan social media addiction.